The Role of School Principal in Providing Organizational Climate in the Elementary Schools in Haifa Area - Haider Al-Omari; Nihaya Weshahi (My University, 2017)
This study aimed to investigate the role of school principal in providing organizational climate in the elementary schools at Haifa Area.The study population consisted of all elementary schools teachers at Haifa Area (totaling (1923) teachers), during the academic year (2014/2015). The study sample consisted of (197) elementary schoolteachers selected randomly by the stratified random sample. The questionnaire consisted of (60) items distributed into six domains of the study: organizational structure, leadership, communication, participation in decision-making, the nature of the job, and technology. The validity and reliability of the questionnaire were verified by the suitable educational and statistical methods. The most important finding of the study is that the role of school principal in providing organizational climate in the elementary schools at Haifa area, was high. The study recommends to promote and stimulate principals to continue providing the organizational climate at their schools, and to benefit from the good organizational climate available at the elementary schools in Haifa at achieving the best levels of performance and achievement.

هدفت الدراسة التعرف إلى دور مدير المدرسة في توفير المناخ التنظيمي في المدارس الابتدائية في منطقة حيفا. وقد تكون مجتمع الدراسة من معلمي ومعلمات المدارس الابتدائية في منطقة حيفا، خلال الفصل الدراسي الثاني للعام الدراسي 2014/2015، والبالغ عددهم (1923) معلماً ومعلمة، وتم اختيار عينة الدراسة بالطريقة العشوائية البسيطة من مجتمع الدراسة، حيث تكونت من (197) معلماً ومعلمة. ولتحقيق أهداف الدراسة تم تطوير استبانة اشتملت على (60) فقرة توزعت على ستة مجالات هي: الهيكل التنظيمي، والقيادة، والاتصالات، والمشاركة في اتخاذ القرار، وطبيعة العمل، والتكنولوجيا. وتم التأكد من صدقها وثباتها. وتوصلت الدراسة إلى عدة نتائج أهمها: أن دور مدير المدرسة في توفير المناخ التنظيمي في المدارس الابتدائية في منطقة حيفا كان كبيراً. وفي ضوء النتائج توصي الدراسة: تعزيز وتحفيز مديري المدارس للاستمرار في توفير المناخ التنظيمي في مدارسهم، وضرورة الاستفادة من المناخ التنظيمي المتوفر في المدارس الابتدائية بمنطقة حيفا في تحقيق أفضل المستويات في الأداء والإنجاز. )البحث مستل من رسالة ماجستير للطالبة: نهاية حسن وشاحي بإشراف الدكتورحيدر محمد العمري، في جامعة جدارا وقد تمت مناقشتها في الفصل الدراسي الأول من العام الدراسي الجامعي 2015/2016.(
دور مدير المدرسة في توفير المناخ التنظيمي في المدارس الابتدائية في منطقة حيفا